Investigation of the Microstructure and Wear Properties of AISI 304 Steel Friction Weldments - Jwan Khalil Mohammed; Ramadhan H Gardi; Dlair O. Ramadan (Zanco Journal of Pure and Applied Sciences, 2020)
In this study, a rotary friction welding technique was used to join austenitic stainless-steel grade AISI 304. The effect of different forging pressure (192.4, 240.5, 288.6 and 384.8 MPa) on wear resistance of AISI 304 were examined using a modified pin on disc tester. The microstructure of the AISI 304 was examined as well using an optical microscope. The wear resistance results of the welded specimens were reported better than as received. The variation of increasing wear loss was uniformly changed with sliding distance. Further, it was noted from the experiments that the wear rate increased with increasing forging pressure in which the minimum wear rate was 3 mm3 at 192.4 MPa while a maximum wear rate (25.823 mm3) occurs at a forging pressure of 384.8 MPa. This is due to the microstructure changes which is decreasing grain size and formation of twin grains and also precipitating carbides.